A Peptide‐Based Supramolecular Hydrogel for Controlled Delivery of Amine Drugs. Issue 22 (18th July 2018) - Wang, Youzhi; Zhang, Yiming; Li, Xinxin; Li, Can; Yang, Zhimou; Wang, Ling
Abstract: Supramolecular hydrogels hold great promise for controlled drug delivery. Herein we report a supramolecular hydrogel based on a peptide bearing a terminal aldehyde. The hydrogel was prepared via an enzyme instructed self‐assembly (EISA) process, and the resulting hydrogels showed ultra‐stable properties in highly acidic or basic aqueous solutions. The hydrogelator could form Schiff bases with amine drugs. Owing to the pH‐responsive properties of Schiff bases, the hydrogels could be used for controlled release of encapsulated amine drugs. Our study provides a peptide‐based hydrogel that may be applied for controlled drug delivery. Abstract : Drug control : An aldehyde‐containing supramolecular hydrogel based on peptides was developed. The hydrogel could be used for controlled delivery of amine drugs.